“Ndableg,” “Ra Sah Ngeyel”: Verbal Offense through Banners about the COVID-19 Pandemic - Aris Munandar (Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
Frustration can be expressed in public in different ways. During the Covid-19 pandemic, the grassroots protestors in Yogyakarta vent their frustrations triggered by the uncertainty through banners, which are simple, yet send messages of the country’s wrongdoings in dealing with the pandemic. This paper discusses verbal violence through negative sentiments expressed in the banners the Yogyakarta grassroots organizations use to respond to the Covid-19 pandemic prevention campaign. This study collected the data from 20 banners displayed in rural areas in Sleman regency, Yogyakarta, during March through April 2020. The analysis applied a sociopragmatic approach. The findings reveal the banners’ strong negative tones targetted to the lower-working class which reflect an inaccurate understanding of the fundamental concept of Covid-19 preventive measures and mitigation. Stigmatization of the lower-working class is underway to hurt the cohesion of society. The negative tones can escalate people’s anxiety, counterproductive to Covid-19 pandemic mitigation as it is against the wisdom of coping with the pandemic with a peaceful mind. Therefore, it suggests that evaluation by the agents of authority is imperative to prevent misunderstanding of the Covid-19 pandemic and build effective communication skills.